The Exploring a New Paradigm: Green Economy Transformation in the Era of Quantum Technology and Artificial Intelligence - Bintang Setiawan, Rizky (The Future of Education Journal, 2024)
This research discusses the role of Quantum Technology and Artificial Intelligence (AI) in supporting the concept of a green economy in the era of the Fourth Industrial Revolution. The green economy concept emphasizes economic growth that considers environmental impact and the sustainability of natural resources. However, complex challenges remain in integrating these technologies to achieve these goals. A Systematic Literature Review (SLR) method was used to collect, evaluate, and synthesize relevant studies. The results show that Quantum Technology and AI have significant potential to enhance operational efficiency, optimize resource use, and accelerate innovation across various economic sectors. However, it is essential to consider the balance between efficiency and environmental sustainability, resource conservation, multi-stakeholder partnerships, ethical considerations, and investment in research and development. The findings indicate that the integration of Quantum Technology and AI can support sustainable economic growth, but requires a holistic and responsible approach. Cross-sector collaboration, ethical thinking, and appropriate investment will be key to formulating a sustainable approach to the development and implementation of these technologies in supporting a green economy.